An improved iterative solution for cooperative distributed MPC. (June 2022) - Wang, Jia; Yang, Ying
Abstract: This note proposes an improved iterative solution of the cooperative distributed model predictive control for large-scale linear systems with interconnected dynamics. In particular, for the purpose of improving the convergence rate, the iteration error is integrated into the iteration process, based on which an algorithm is proposed to optimize the gain matrix of the iteration error. The effectiveness of the proposed approach is verified through the numerical simulation.